Analysis of the Surface of the Alloy Ti-6Al-4V Treated by Plasma Spray Deposition for Use as a Biomaterial - Alencar, A. C. [UNESP]; Melnikov, P. [UNESP]; Santos, M. L. dos [UNESP]; Riccardi, C. S. [UNESP]; Guastaldi, A. C. [UNESP] (Amer Scientific Publishers, 2015)
The surface of the Ti-6Al-4V alloy for implants was studied before and after the surface modification using the spraying of titanium dioxide with plasma-gun. The purpose of producing such a coating was to create an appropriate metal support having large specific area in order to improve the integration of the regenerated bone and the implant used for the prostheses. The characterization have been carried out by chemical analysis and X ray diffraction study of the Alloy, of the starting oxide, TiO2 and of the coating after the deposition. The coating X ray pattern showed the presence of both defectuous titanium monoxide and titanium sesquioxide, Ti2O3. According to the morphology studies performed by scanning electron microscopy, the coating surface is porous and exhibits high homogenity. Point EDX analysis permitted to detect diffusion the oxygen, titanium, aluminium and vanadium in the substrate/coating interface area. Presence of TiO and Ti2O3 in the coating is related with the titanium dioxide thermal decomposition in the plasm spray jet, followed by the recombination of its components to produce the sesquioxide, Ti2O3 and the solid solutions of the composition TiO1-x formed because of oxygen insertion. The porous morphology and the presence of the above phases in the coating allow recommending this technique for the implant osseointegration in clinical experiments, Today definition of osseointegration is the apparent direct attachment or connection of vital osseous tissue to the surface of an implant, without intervening connective tissue.
Keywords: Ti-6Al-4V Alloy; Plasma Spray; Surface Modification; Titanium Oxides; Biomaterials